FARMERS’ PERCEPTION OF SOIL DEGRADATION IN SEMI-ARID AREAS OF KATSINA STATE, NORTHERN NIGERIA - Abdulrashid, Lawal (FUDMA Journal of Sciences, 2023)
Perspectives of farmers on indicators and causes of soil degradation and the measures used in conserving the soil fertility were investigated in some selected villages in six local government of Katsina State. Household survey, key informants interview; focus group discussion and field observation were used in the data collection. The result indicated that farmers have an array of indicators for assessing the extent of soil degradation in their farms and also identified and explained the causative factors responsible for the phenomenon. Majority of the farmers prefer to use agronomic/biological conservation compare to mechanical measures which require a lot of materials hence costly, difficult to make and maintain. It is also found that individual views on soil degradation are influenced by many factors, thus when planning any programme to remediate soil degradation one must take cognizance of farmers’ differences of environmental knowledge and their holistic perception of the problem